2022
DOI: 10.3934/dsfe.2022009
|View full text |Cite
|
Sign up to set email alerts
|

The informative value of central banks talks: a topic model application to sentiment analysis

Abstract: <abstract><p>Central banks communication has lately become an important tool to guide expectations and its impact on the economy has been acknowledged by the literature. Nowadays central banks speeches face an increasing variety of topics, which are not discriminated by text analysis. In this paper we build a topic-weighted central bank sentiment index as a combination of machine learning and text analysis techniques to investigate large datasets. First, we develop a methodological framework to gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Moreover, the analysis revealed that a rate hike (cut) and a hawkish (dovish) monetary policy statement are associated with higher odds of observing a restrictive (accommodative) decision at Banxico's next meeting. These results are consistent with recent research empirically testing the same hypothesis in other cbs (see Astuti et al, 2022;and Priola et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, the analysis revealed that a rate hike (cut) and a hawkish (dovish) monetary policy statement are associated with higher odds of observing a restrictive (accommodative) decision at Banxico's next meeting. These results are consistent with recent research empirically testing the same hypothesis in other cbs (see Astuti et al, 2022;and Priola et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with other relevant papers (see Picault & Renault, 2017;Baranowski et al, 2021;Priola et al, 2022;and Astuti et al, 2022) that evaluate the predict effects of cb communication on future policy decisions. This study contributes to the existing literature by focusing on these aspects for the Mexican cb, utilizing recent nlp techniques outlined in the literature.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations